Penafsiran Ayat-ayat tentang Tempat yang Diberkahi dalam Al Qur’an (Analisis Tafsir Maqasidi) - Fathoni, Idzhar (Darul Yasin Al Sys, 2024)
The purpose of this research is to find out the places that are blessed in the Quran by using the principles of the maqasidi interpretation methodology constructed by Abdul Mustaqim. This research uses library research that focuses on aspects of theology, history, and several other influential figures. The problem to be researched is how the theologian interpret the verses about the blessed place in the Quran, and their reading uses the maqasidi Abdul Mustaqim interpretation methodology. The results of the research show that blessings do not always have a material meaning, but also in the sense of immaterial virtues uhrawi. One of them is the blessing of places that have been informed in the Quran, including: blessings on the earth, Mecca, and Syria. Through the maqasidi Abdul Mustaqim interpretation methodology, verses about blessed places have aspects of protecting the environment (hifz al-bi'ah), and aspects of protecting the state (hifz ad-daulah) are not only protective (min haits al-'adam) but also productive/development (min haits al-wujud).